The grave artist - Deaver, Jeffery; Maldonado, Isabella, 1965- (Sanchez & Heron, 2025)
"A wedding reception is coming to a close in the Hollywood Hills when the blissful day is shattered by the death of one of the newlyweds. Though the incident appears to be an accident, Homeland Security Investigations agent Carmen Sanchez and her partner, security expert Jake Heron, discover that the tragedy is the third in a series of similar deaths and conclude something far more sinister is at play. The two uncover chilling evidence pointing to a serial killer who has taken evil to the next level. Dubbed the Honeymoon Killer, this man isn't interested in his victims but in creating his own macabre masterpiece from their graves, focused on the survivors and reveling in their grief. And now his dark obsession has turned to Carmen and Jake."--